2010
DOI: 10.3945/ajcn.2010.29305
|View full text |Cite
|
Sign up to set email alerts
|

High habitual dietary α-linolenic acid intake is associated with decreased plasma soluble interleukin-6 receptor concentrations in male twins

Abstract: Background: a-Linolenic acid (ALA) is associated with a low risk of cardiovascular disease; however, the underlying mechanism is not completely known. Objective: The objective was to examine whether habitual dietary ALA intake is associated with plasma concentrations of inflammatory biomarkers after control for shared genetic and common environmental factors. Design: We cross-sectionally studied 353 middle-aged male twins. Habitual diet was assessed with the Willett food-frequency questionnaire. Fasting plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…For example, a recently published cross-sectional study that included 353 male twins found that a one gram increment in habitual ALA intake was associated with an 11% decrease in plasma soluble interleukin-6 receptor concentrations, which by virtue of decreasing inflammation, could reduce CHD risk [76]. The reader is referred to the references for perspectives on whether vegetarians are at a disadvantage by not consuming DHA and EPA-containing fish [77,78].…”
Section: Role Of Soy In Reducing Vegetarian Risk Of Chronic Diseasementioning
confidence: 99%
“…For example, a recently published cross-sectional study that included 353 male twins found that a one gram increment in habitual ALA intake was associated with an 11% decrease in plasma soluble interleukin-6 receptor concentrations, which by virtue of decreasing inflammation, could reduce CHD risk [76]. The reader is referred to the references for perspectives on whether vegetarians are at a disadvantage by not consuming DHA and EPA-containing fish [77,78].…”
Section: Role Of Soy In Reducing Vegetarian Risk Of Chronic Diseasementioning
confidence: 99%
“…Dai et al [20•] examined habitual ALA intake and plasma concentrations of inflammatory markers, including IL-6 and sIL-6R, in 353 middle-aged men in the United States who were recruited from a twin registry. ALA intake, assessed by the Willett questionnaire, ranged from 0.2 to 2 g/d, and was significantly inversely related to plasma sIL-6R independent of shared genetic factors and a wide range of potential confounders.…”
Section: Observational Studies On Ala Intake and Cardiovascular Riskmentioning
confidence: 99%
“…Although studies are not consistent, long-term and high ALA intake has been associated with decreased risk of cardiovascular disease [ 5 , 6 , 7 , 8 , 26 ]. Inflammation is a pathophysiologic pathway for cardiovascular disease, and several studies support reduced systemic inflammation in groups with high dietary ALA intake [ 11 , 12 , 13 , 26 ]. A cross-sectional study of 353 middle-aged male twins showed that a 1-g increment in habitual dietary ALA intake was associated with 11% lower concentrations of the IL-6 soluble receptor (sIL-6R) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a pathophysiologic pathway for cardiovascular disease, and several studies support reduced systemic inflammation in groups with high dietary ALA intake [ 11 , 12 , 13 , 26 ]. A cross-sectional study of 353 middle-aged male twins showed that a 1-g increment in habitual dietary ALA intake was associated with 11% lower concentrations of the IL-6 soluble receptor (sIL-6R) [ 26 ]. Cytokine production in cultured peripheral blood mononuclear cells (PBMCs) is decreased following high ALA diets in hypercholesterolemic subjects [ 27 ].…”
Section: Discussionmentioning
confidence: 99%